Characterization of a Planar Solid Oxide Cell Stack Operated at Elevated Pressure. Issue 14 (19th November 2016) - Jensen, S. H.; Graves, C.; Chen, M.; Hansen, J. B.; Sun, X.
Abstract : As global and local energy production becomes more dependent on intermittent renewable sources like wind and solar, efficient and reversible conversion of electricity to storable fuels becomes increasingly important. Solid oxide cells (SOCs) are interesting in this context since they can be operated either as electrolyzers (SOEC) to convert electricity to fuels such as hydrogen or methane, and as fuel cells (SOFC) to convert fuels to electricity. Both productivity and conversion efficiency can be improved if the SOC operation pressure can be increased from ambient pressure to 10–30 bar. In this paper we characterize an SOC stack operated at pressures from ambient pressure to 10 bar. The pressure dependency of stack temperature, cell area specific resistance (ASR), current-voltage (iV) curves, stack impedance spectra and pressure drop across the stack and heat exchangers is analyzed in this paper. Additionally, the expected impact on the hydrogen production efficiency and cost is discussed.